2020
DOI: 10.3171/2018.12.jns181798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycolysis inhibition by miR-448 on glioma radiosensitivity

Abstract: OBJECTIVEAlthough glucose metabolism reengineering is a typical feature of various tumors, including glioma, key regulators of glycolytic reprogramming are still poorly understood. The authors sought to investigate whether glycolysis inhibition by microRNA (miR)–448 increases radiosensitivity in glioma cells.METHODSThe authors used glioma tissue samples from glioma patients, cells from glioblastoma (GBM) cell lines and normal human astrocyte cells, and subcutaneous tumor–bearing U87 cells in mice to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…A similar mechanism was reported for miR-448 in glioma cells. miR-448 directly targeted HIF-1α, which led to inhibition of proteins involved in glycolysis: HK1, HK2, LDHA [64]. miR-133b sensitized NSCLC cells to IR and negatively regulated glycolysis.…”
Section: Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar mechanism was reported for miR-448 in glioma cells. miR-448 directly targeted HIF-1α, which led to inhibition of proteins involved in glycolysis: HK1, HK2, LDHA [64]. miR-133b sensitized NSCLC cells to IR and negatively regulated glycolysis.…”
Section: Mirnasmentioning
confidence: 99%
“…Mcl-1 Apoptosis GBM, cervical cancer [51] miR-199a Beclin-1, DRAM1 Autophagy Breast cancer [52] miR-200c UBQLN1 Autophagy Breast cancer [53] miR-203a ATM Apoptosis, cell cycle, migration Ovarian cancer [54] miR-205 TP53INP1 Autophagy Prostate cancer [26] miR-214 ATG12 Autophagy CRC * [55] miR-216a Beclin-1 Autophagy Pancreatic cancer * [56] miR-222 RAD51 DSB repair Ovarian cancer [34] miR-223 ATM -Glioma * [57] miR-301a Wnt Wnt/β-catenin, migration ESCC [58] miR-302a AKT, RAD52 -Breast cancer * [59] miR-320a STAT3 Apoptosis, metastasis NSCLC * [60] β-catenin Wnt/β-catenin Cervical cancer [61] miR-324-3p Wnt2B Wnt/ β-catenin NPC [62] miR-421 ATM DSB repair SCC [63] miR-448 HIF-1α Glycolysis Glioma [64] miR-449a LDHA Glycolysis, apoptosis Lung cancer [65] miR-449a c-MYC Cell cycle Prostate cancer * [66] miR-450a DUSP10 Autophagy ESCC * [67] miR-634 STAT3 Apoptosis Breast cancer [68] miR…”
Section: Introductionmentioning
confidence: 99%
“…The reasons at the gene level include the following two types: the decrease of apoptotic genes or the increase of the expression of anti-apoptotic genes and proliferating genes, and the enhancement of genes related to DNA damage repair, or the expression of cell cycle regulatory genes is dysregulated [6,7,17,18]. Many studies have shown that miRNAs participate in tumor radiation resistance through the above mechanisms [19][20][21].…”
Section: Mechanism Of Radiotherapy Resistance In Nasopharyngeal Carcimentioning
confidence: 99%
“…160 Regarding the effects of chemotherapy and radiotherapy, HIF-1α signaling participated in regulating effectiveness of irradiation and temozolomide of glioma via the glycolytic process. 158,161 Surprisingly, more and more regulators have been detected in the functional activities of HIF-1α in glioma. The hypoxic condition could contribute to the upregulation of HIF-1α via elevating the expression of TIGAR, while prolyl hydroxylation of HIF-1α would happen under normoxic conditions.…”
Section: Interplay Of Transcription Factors In Aerobic Glycolysis Hif-1αmentioning
confidence: 99%